Arcus in Horace, Carm. 3. 26. 7 - Keyer, Denis (Hyperboreus, 2017)
The author defends G. P. Bidder’s suggestion that arcus in Hor. Carm. 3. 26. 7 implies a drill bow. An important argument in its favour is that this meaning of arcus has been attested in Greek-Latin glosses (CGL II [1888] 244. 35: αρις arcus).